Consistent assessment of neutron-induced activation of 93Nb - Avrigeanu, Vlad; Avrigeanu, Marilena (Frontiers in Physics, 2023)
A concurrent assessment of all measured excitation functions for various reactions induced by neutrons on 93Nb, in addition to the results of TENDL-2021 and default parameters in TALYS-1.96, is given in this work. We use consistent parameter sets that were formerly obtained or validated by the analysis of other independent data, while no empirical rescaling factors of γ and/or neutron widths have been used. The correlation between the measured error bars of the primary data providing the consistent input parameters and the final uncertainty bands of the calculated results have been pointed out. At the same time, a proper account in this work of all available data for competitive reaction channels prevented compensation effects of less accurate model parameters. Remaining questions and the need for additional measurements are emphasized.